Acquired Skin Fragility Syndrome in a Juvenile Cat Following a Routine Ovariohysterectomy - Karakaya Bilen, Ebru; Akgül, Mustafa Barış (Acta Scientiae Veterinariae, 2021)
Background: Acquired skin fragility syndrome (ASFS) is a rare condition, which is characterized by spontaneous fragility of the skin and an absence of hyperextensibility. Even though the real pathogenesis of ASFS remains unknown that is reported generally with some iatrogenic causes and severe diseases. Thus, based on the clinical findings this is the first report of describes the case and treatment of feline acquired skin fragility syndrome following a routine ovariohysterectomy. Case: An 8-month-old domestic shorthair female cat was brought to the Siirt University Animal Health Application and Research Center for ovariohysterectomy operation. Before the operation physical examination of the animal revealed body temperature, heart rate, respiratory rate, the color of mucosas, and lymph nodes were determined normally. Besides, there is no hematological and biochemical problem detected. The cat had no previous history of several infections or systemic disease. A routine ovariohysterectomy procedure was applied under general anesthesia and the cat was discharged on the same day. Three days after that a spontaneously developed cutaneous laceration below the left scapular region was determined by the cat owner. During the clinical examination, it was determined that the cat was sensitive to touch against the left scapular area. Multiple spontaneous skin tear was revealed over the left scapular region while shaving for better inspection but did not obtain any problem with incision line. To identify the underlying cause of skin tearing, hematological and biochemical tests were done but the animal’s results were found within the normal references. Also, rapid blood tests were performed for feline leukemia virus and immunodeficiency virus, and none of them were positive. Additionally, the skin was not hyperextensible. Although the clinicopathological abnormalities were observed on the skin, there were no abnormalities in the vital signs of the cat. Based on the clinical status of the cat, daily regular wound cleaning and a wet-to-dry bandage were applied for two weeks. Skin therapy based on the use of dexpanthenol, vitamin E, and vitamin C with zinc was preferred to improve skin health. All lesions on the skin of the cat completely recovered and a follow-up visit for several weeks was recommended to the cat owner. Discussion: There have been reports that acquired skin fragility syndrome may be related to hepatic diseases, some feline viral infections, hyperadrenocorticism, or use of a long time progestational drugs. Also, acquired skin fragility syndrome can be seen in a congenital disorder known as cutaneous asthenia which is described generally in young cats. Cutaneous asthenia and acquired skin fragility syndrome are difficult to distinguish from each other even though histological examination was made. Although the cat in this report is young, there was no history of skin problems and skin hyperextensible until presentation. No specific treatment protocol described for this skin problem has been reported. Moreover, vitamins and minerals may be used for wound treatment and strengthening the skin. Ovariohysterectomy is the most common surgical technique used for sterilization of cats however; it can cause some complications, such as acute stress. Unfortunately, the exact etiology is not detected in this case report but it is thought to be that stress of ovariohysterectomy might be triggered to spontaneous skin tearing.